2017
DOI: 10.1186/s12885-017-3823-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of the β2 integrin on tumor cells is associated with a reduction in liver metastasis of colorectal cancer in mice

Abstract: BackgroundLymphocyte Function-Associated Antigen-1 (LFA-1; CD18/CD11a) is one of the main adhesion molecules used by immune cells to infiltrate the liver under inflammatory conditions. Recently, the expression of this integrin has also been reported on several solid tumors, including colorectal cancer. However, its functional role in the metastatic progression to the liver remains unknown. Using in vitro assays and an experimental orthotopic in vivo model of liver metastasis, we aimed to elucidate the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 41 publications
2
27
0
Order By: Relevance
“…The involvement of ICAM-1 in tumor cell adhesion to the hepatic sinusoidal wall was confirmed by in vivo retention assays. One day after intrasplenic inoculation, tumor cells are already retained in the liver 16 . At this time point, ICAM-1-silenced livers contain 50% fewer tumor cells than livers from mice injected with scramble siRNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of ICAM-1 in tumor cell adhesion to the hepatic sinusoidal wall was confirmed by in vivo retention assays. One day after intrasplenic inoculation, tumor cells are already retained in the liver 16 . At this time point, ICAM-1-silenced livers contain 50% fewer tumor cells than livers from mice injected with scramble siRNA (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that activated LSECs release inflammatory factors after ICAM-1 ligation with tumor LFA-1, that correlates with a decreased lymphocyte cytotoxic activity 15 . Moreover, decreased expression of LFA-1 on tumor cells is associated with a reduction in liver metastasis of colorectal cancer in mice 16 . Indeed, a role for endothelial ICAM-1 on tumor transmigration could be envisioned as ICAM-1 ligation by LFA-1 receptor on bladder carcinoma cells leads to HUVEC cell retraction and transmigration 17 .…”
Section: Introductionmentioning
confidence: 95%
“…Whereas LFA-1 expression is confined to leukocytes under normal conditions [6], tumor cells may express this β2 integrin as well, shown to elevate their metastatic activity [328]. The surface glykoprotein CD44 is frequently expressed by tumor cells and mediates tumor cell migration by binding collagen as a constituent of the ECM [329].…”
Section: β2 Integrin Expression By Tumor Cellsmentioning
confidence: 99%
“…Instead of extracting genes merely associated with survival outcomes using the Cox regression analysis, we developed our prediction model based on recurrence-specific genes using the machine learning algorithm. Most genes included in our final prediction model were reported to be related to survival in lung cancer or other cancers [ 34 42 ], which indicates the rationality of our prediction model. For example, high expression of P4HA1 and S100A10 was reported to be associated with dismal survival outcomes in LUAD [ 36 , 38 ].…”
Section: Discussionmentioning
confidence: 80%